CLIMATE CHANGE LITIGATION: COMPARATIVE PERSPECTIVES ON ENVIRONMENTAL JUSTICE ACROSS JURISDICTIONS - Yeni Santi; Tubagus Angling Perdana (Adisam Publisher, 2025)
This study aims to analyze the development of climate change litigation from a comparative perspective, emphasizing how environmental justice principles are interpreted and applied across jurisdictions. Using a literature review, the study examines court decisions, legal frameworks, international instruments, and academic research addressing the role of litigation as a means of accountability in addressing the climate crisis. The study demonstrates that, despite differences in social, economic, and political contexts across countries, global climate change litigation demonstrates a trend of strengthening the position of civil society and vulnerable groups in demanding equitable environmental protection. A comparison across jurisdictions reveals that countries with robust environmental legal frameworks and responsive judicial systems are better able to utilize litigation as an effective tool to encourage commitments to climate mitigation and adaptation. Furthermore, the study finds that the concept of environmental justice is increasingly becoming a central focus in climate litigation, particularly regarding the protection of the rights of future generations, the equitable distribution of climate risks, and the responsibilities of states and corporations. This literature review confirms that climate change litigation functions not only as a legal mechanism but also as a social process that drives public policy transformation. Therefore, a comparative understanding across jurisdictions can provide important insights for strengthening global climate governance and more comprehensively protecting environmental justice.